Manager’s perception of Artificial Intelligence : Case of Moroccan organizations. - MOUSSAOUI Khaoula; IBENRISSOUL Nafii (African Scientific Journal, 2025)
Abstract Nowadays, the evolution of management in the context of modern technologies has become a necessity, particularly with the emergence of artificial intelligence (AI). This study aims to explore the managers’ perception of AI and highlights its advantages and challenges. The research is based on a literature review and a semi-structured questionnaire survey with 23 managers in different sector of activity. By understanding the manager’s perception of perceptions, organizations can foster a positive and informed approach to AI integration, leading to a successful application and enhancing decision-making processes. It also contributes to develop performance and leverage competitive advantage. These findings clarify the manager’s perception of artificial intelligence in the Moroccan context, which would have several implications on organizations. Keywords: Artificial intelligence, manager’s perception, Decision-making, Human-AI technology, Competitive advantage, Performance.